2013
DOI: 10.1002/ajoc.201300077
|View full text |Cite
|
Sign up to set email alerts
|

Iridium/NMDPP Catalyzed Asymmetric Ring‐Opening Reaction of Oxabenzonorbornadienes with Phenolic or Naphtholic Nucleophiles

Abstract: Open up: An [Ir(COD)Cl]2/ (S)‐NMDPP (COD=1,5‐cyclooctadiene; NMDPP=neomenthyldiphenylphosphine) complex catalyzes asymmetric ring‐opening reactions of oxabenzonorbornadienes with phenolic or naphtholic nucleophiles efficiently. Up to 96 % yield and 88 % ee was achieved. DMF=N,N‐dimethylformamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Halide and triflate salts such as NH 4 F, Et 3 N∙HCl, NH 4 Br, NH 4 I, Bu 4 NI, and AgOTf were also used as additives to enhance the enantioselectivities of the ARO reaction. Recently, our group demonstrated that iridium-catalyzed asymmetric ring-opening of oxa- and azabicyclic alkenes with nitrogen- or oxygen-based nucleophiles, such as amines, alcohols, phenols and Grignard reagents [62,63,64,65,66,67,68,69,70,71,72,73,74]. Furthermore, a new iridium-monophosphine catalyst was found to be efficient for asymmetric ring-opening of benzonorbornadiene with amines, providing a series of chiral substituted dihydronaphthalenes in high yields (up to 98%) and excellent enantioselectivities (>99% ee ) [71].…”
Section: Introductionmentioning
confidence: 99%
“…Halide and triflate salts such as NH 4 F, Et 3 N∙HCl, NH 4 Br, NH 4 I, Bu 4 NI, and AgOTf were also used as additives to enhance the enantioselectivities of the ARO reaction. Recently, our group demonstrated that iridium-catalyzed asymmetric ring-opening of oxa- and azabicyclic alkenes with nitrogen- or oxygen-based nucleophiles, such as amines, alcohols, phenols and Grignard reagents [62,63,64,65,66,67,68,69,70,71,72,73,74]. Furthermore, a new iridium-monophosphine catalyst was found to be efficient for asymmetric ring-opening of benzonorbornadiene with amines, providing a series of chiral substituted dihydronaphthalenes in high yields (up to 98%) and excellent enantioselectivities (>99% ee ) [71].…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our previous research on the ring opening reaction of oxa- or aza- benzonorbornadienes, we turned our attention to the asymmetric ring addition reaction, which is still underdeveloped. We embarked on this investigation using oxabenzo­norborna­diene 1a and thiophenol 2a as benchmarked on substrates.…”
mentioning
confidence: 99%